Methodological assumptions for modelling the spread of pollutants in the air from incidental waste fires - Cuske, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the possibilities of applying the methodology of modelling the spread of pollutants in the air for the processes of uncontrolled waste combustion with the use of the Gaussian Dispersion Model (1st generation plume), simultaneously modifying the assumptions for input data in regard to the degree of emission and meteorogical parameters assumed for modelling. The model has been adapted to parameters of the assumptions of the Source Characterisation Model (SCM). The publication indicates the suitability of using the described methodology in specific conditions to forecast the spread of a pollution cloud.
Keywords: modelling the spread of air pollutans; uncontrolled waste fires; the Pasquill model